E-IMR: e-health added to face-to-face delivery of Illness Management & Recovery programme for people with severe mental illness, an exploratory clustered randomized controlled trial - Titus A. A. Beentjes; Peter J. J. Goossens; Hester Vermeulen; Steven Teerenstra; Maria W. G. Nijhuis-van der Sanden; Betsie G. I. van Gaal (BMC, 2018)
Abstract Background E-mental health holds promise for people with severe mental illness, but has a limited evidence base. This study explored the effect of e-health added to face-to-face delivery of the Illness Management and Recovery Programme (e-IMR). Method In this multi-centre exploratory cluster randomized controlled trial, seven clusters (n = 60; 41 in intervention group and 19 in control group) were randomly assigned to e-IMR + IMR or IMR only. Outcomes of illness management, self-management, recovery, symptoms, quality of life, and general health were measured at baseline (T0), halfway (T1), and at twelve months (T2). The data were analysed using mixed model for repeated measurements in four models: in 1) we included fixed main effects for time trend and group, in 2) we controlled for confounding effects, in 3) we controlled for interaction effects, and in 4) we performed sub-group analyses within the intervention group. Results Notwithstanding low activity on e-IMR, significant effects were present in model 1 analyses for self-management (p = .01) and recovery (p = .02) at T1, and for general health perception (p = .02) at T2, all in favour of the intervention group. In model 2, the confounding covariate gender explained the effects at T1 and T2, except for self-management. In model 3, the interacting covariate non-completer explained the effects for self-management (p = .03) at T1. In model 4, the sub-group analyses of e-IMR-users versus non-users showed no differences in effect. Conclusion Because of confounding and interaction modifications, effectiveness of e-IMR cannot be concluded. Low use of e-health precludes definite conclusions on its potential efficacy. Low use of e-IMR calls for a thorough process evaluation of the intervention. Trial registration The Dutch Trial Register (NTR4772)